A Moderated Mediation Effect of Stress-Related Growth and Meaning in Life in the Association Between Coronavirus Suffering and Satisfaction With Life: Development of the Stress-Related Growth Measure - Yıldırım, Murat; Arslan, Gökmen (Frontiers in Psychology, 2021)
As previous pandemics, the coronavirus disease 2019 (COVID-19) has direct and indirect effects on mental health and well-being. The purpose of the current study was to examine whether meaning in life mediated the association between coronavirus suffering and satisfaction with life, and whether stress-related growth moderated the mediating effect of meaning in life on the association between these variables. Stress-related Growth Measure was also conducted for the purpose of this study. The participants were 402 (66% women) young adults who completed the Suffering Measure during COVID-19, Meaningful Living Measure, Satisfaction with Life Scale, and SGM. The results indicated that the SGM has adequate psychometric properties with unidimensional structure of stress-related growth in the face of adversity. Moderated mediation analysis revealed that coronavirus suffering directly influenced satisfaction with life as well as indirectly by its effect on meaning in life. Additionally, stress-related growth was found as moderator in the relationship between coronavirus suffering-meaning in life and coronavirus suffering-satisfaction with life. These results suggest that meaning in life mitigates the effect of coronavirus suffering on satisfaction with life and this mediating effect is moderated by stress-related growth in young adults. While meaning in life helps to explain the relationship between coronavirus suffering and satisfaction with life, the stress-related growth functions as a protective factor against the adverse effect of coronavirus experiences.